2022
DOI: 10.48048/tis.2022.3032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toxicity and Anti-Oxidation Activity of the Extracts from Halymenia durvillei

Abstract: Halymenia durvillei (HD), a marine red alga, is believed to have potentials for pharmacological, nutritional and cosmetic applications. However, such potentials are acceptable only when their extracts are devoid of any adverse effects on human health. No previous research has been conducted the toxicity and anti-oxidation capacity of HD. Thus, the aim of this work was to investigate toxicity and anti-oxidation activities of HD extracts. In this study, the toxicity and anti-oxidation capacity of 5 fractions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The results implied that HDHE inhibited proliferation of A172 cells at concentrations lower than IC50. HDHE concentration at IC50 level tested in A172 cells has less toxic to normal mammalian cells like mouse macrophage, keratinocyte and hepatocyte as previously reported [6]. Thus, cytotoxic concentration of HDHE may appropriate to inhibit proliferation of A172 cells, while safe to normal cells.…”
Section: Cytotoxicity and Proliferation Effectssupporting
confidence: 62%
See 1 more Smart Citation
“…The results implied that HDHE inhibited proliferation of A172 cells at concentrations lower than IC50. HDHE concentration at IC50 level tested in A172 cells has less toxic to normal mammalian cells like mouse macrophage, keratinocyte and hepatocyte as previously reported [6]. Thus, cytotoxic concentration of HDHE may appropriate to inhibit proliferation of A172 cells, while safe to normal cells.…”
Section: Cytotoxicity and Proliferation Effectssupporting
confidence: 62%
“…HD extracts might be beneficial to applied as disease-preventing substances as well as anticancer agents due to the enrichment of bioactive ingredients. The hexane solvent extract from HD showed high antioxidant activity tested by DPPH and ABTS assays [6]. The extract, which enriched with n-hexadecanoic acid (palmitic acid) could inhibited proliferation against MDA-MB-231 triple-negative breast cancer cells by induction of apoptotic and autophagic cell death and associated with endoplasmic reticulum stress pathway [7].…”
Section: Introductionmentioning
confidence: 99%
“…The present study examined the anticancer properties of marine red algae, H. durvillei. Previous studies revealed the biological effects of extracts from H. durvillei extracts, including antibacterial (Kasmiati et al, 2022), antioxidant (Chaiwichien et al, 2022), antidiabetic, and anti-wrinkling (Arguelles, 2022). Recently, we successfully identified the chemical compositions of HDEA.…”
Section: Discussionmentioning
confidence: 99%
“…HDEA was prepared as previously described (Manohong et al, 2021;Chaiwichien et al, 2022). Briefly, the dried 1.1 kg of H. durvillei was milled and macerated with 5 L of 95% ethanol for one week, and the solvent was evaporated using a rotary evaporator.…”
Section: Extraction and Isolationmentioning
confidence: 99%
See 1 more Smart Citation